The centralization of the worship of Yahweh according to the Jewish and Samaritan Pentateuchs : a textual and theological study - Paulo, Bonifacio (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.